Blurred Boundaries: A Day in the Life of a Teacher - Victoria Hunter Gibney; Kristine L. West; Seth Gershenson (Institute of Labor Economics (IZA), 2022)
The burnout, stress, and work-life balance challenges faced by teachers have received renewed interest due to the myriad disruptions and changes to K-12 schooling brought about by the COVID-19 pandemic. However, even prior to the pandemic relatively little was known about teachers' time use outside of the classroom, the blurring of work and home boundaries, and how teachers compare to similar professionals in these regards. We use daily time-diary data from the American Time Use Survey (ATUS) for 3,227 teachers and 1,947 professionals in similarly prosocial occupations from 2003 to 2019 to examine occupational differences in time use. Compared to observationally similar non-teachers, teachers spend significantly more time volunteering at their workplace and completing work outside the workplace. On average, teachers spend 12 more minutes working outside of the workplace on weekdays than observably similar non-teachers, and 39 more minutes on weekends. The weekend disparity is particularly large among secondary school teachers. This suggests that before the widespread switch to online and hybrid learning necessitated by the COVID pandemic, teachers were already navigating blurrier work-life boundaries than their counterparts in similar professions. This has important implications for teacher turnover and for the effectiveness and wellness of teachers who remain in the profession.
Keywords: I2; J22; 330; teacher labor supply; time use